2011
DOI: 10.1097/sla.0b013e31823009e6
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Versus Open Anterior Abdominal Wall Hernia Repair

Abstract: Laparoscopic hernia repair is infrequently used and associated with lower 30-day morbidity, particularly when hernias are complicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(27 citation statements)
references
References 29 publications
0
26
0
1
Order By: Relevance
“…In contrast to most studies in the literature that reported SSI rates after only single anatomic site procedures 5;6;813 or after procedures that included a mixture of anatomic sites, 7 we applied a uniform method to identify SSIs after categorizing the site and surgical approach in order to compare infection rates across different anatomical sites and surgical approaches. In addition, the use of claims data allowed identification of SSIs after discharge across the spectrum of health care providers.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to most studies in the literature that reported SSI rates after only single anatomic site procedures 5;6;813 or after procedures that included a mixture of anatomic sites, 7 we applied a uniform method to identify SSIs after categorizing the site and surgical approach in order to compare infection rates across different anatomical sites and surgical approaches. In addition, the use of claims data allowed identification of SSIs after discharge across the spectrum of health care providers.…”
Section: Discussionmentioning
confidence: 99%
“…We tested the hypothesis that antibiotic treatment of uncomplicated acute appendicitis was noninferior to appendectomy. Based on prior studies, 13 we as-sumed that there would be a 24% difference in treatment efficacy between the surgical and antibiotic groups.…”
Section: Objectivementioning
confidence: 99%
“…National Scandinavian registries, like the Swedish Hernia Database and the Danish Hernia Database on hernia surgery, have demonstrated this [14]. Also multicentre databases like the Veterans Affairs Medical Centers database and the National Surgical Quality Improvement Program database have been able to detect poor outcome results in hernia surgery [57]. …”
Section: Introductionmentioning
confidence: 99%